Effects of hot water pre-extraction on surface properties of bagasse soda pulp - Cordeiro, Nereida (2021)
In this work, the effects of hot water pre-extraction of depithed bagasse on the soda pulping and surface properties were studied. The conditions of hot water pre-extraction were: maximum temperature 170 °C, heat-up time 90 min, time at maximum temperature 10 min, and solid to liquor ratio (S:L) 1:8. Consequently, the pre-extracted and un-extracted bagasse chips were subjected to soda pulping at 160 °C for 1h with 11, 14 and 17% active alkali charge and an S:L of 1:5. The results showed that the hot water pre-extraction increased bagasse surface texture porosity by hemicellulose degradation. Therefore, the delignification was faster for pulping of pre-extracted samples. At a certain charge of alkali, pre-extracted samples showed higher screened yield and lower Kappa number. For instance, at 17% alkali charge, pre-extracted bagasse gave 11.3% higher pulp yield compared with the un-extracted ones. Inverse gas chromatography (IGC) results showed that the hot water pre-extraction changed the active sites on the bagasse surface, decreasing the dispersive energy and the basicity character, and affected the particle morphology. The pulping process decreased the hydrophobicity and the basicity of the bagasse surface. The surfaces of un-extracted and pre-extracted bagasse pulps had similar properties but different morphology. The pulps present higher surface area and permeability with more reactive capacity.